The Opinions of Graduated Students of Medicine on the Amount of Compatibility Existing between the Programs of Clinical Education and their Occupation Needs in Kerman - Z Ghazanfari (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: The significance of the occupation of medical doctors has given great importance to the methods used in medical education of training. The opinions of graduated students of medical science is fruitful in disclosing whether the clinical trainings are effective for medical services or not and to discover what its possible shortcomings are. Therefore the following study was performed to determine the opinions of graduated students of medicine on the amount of compatibility existing between the programs of clinical education and their occupation needs.METHODS: The cross-sectional study was done on 200 graduated students of general medicine from the year 1997 and after, in Kerman University of medical sciences, Kerman, Iran. The research was held by the use of a questionnaire which had 2 parts. The first was a demographic data gathering and the second included 25 questions on technical and communication skills. After collecting the data, graduated students were required to utter the quality of the trainings and the trainer in both sections of the questionnaire. The answers were rated as sufficient, almost sufficient and not sufficient.FINDINGS: The results revealed that 69% of the students believed the technical skill trainings were almost sufficient in relative to their occupation needs. Self training was the most to gain significance for being an effective procedure in training among 10 out of the 15 technical skills (92%). For two of the communication skills 72% of the students claimed the given trainings to be satisfying and as for 8 other skills, 70% of the graduated students believed the trainings were almost sufficient. For 8 skills of the total communication skills the trainers had the most influence. For 2 remaining skills the percentage of the effectiveness of self trains was higher than of that of the trainer and personal trainings.CONCLUSION: The data conveyed that the existing adjustment between clinical training programs and the occupational needs of the graduated students is not completely adequate and satisfying. Thus the need for elevating the quality of clinical trainings is emphasized to increase the effectiveness of educational and training programs for the future occupation of medical students.